PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 18 BABUSSALAM KECAMATAN MANDAU KABUPATEN BENGKALIS - Jufrina '; Zariul antosa; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research problem is the low student learning outcomes that students are still less active and less passion, less attention in learning when the teacher explains, quickly get bored and talking with your seatmate. Students are less able to associate lessons learned with lessons to be learned. And things like that happen it causes the student's knowledge does not develop, the skills are not trained and students are not accustomed to solve its problems alone. Activities of teachers at the first meeting of the first cycle is 66.67% less category, decreased in the first cycle of the second meeting with a value of 79.17% categorized enough. While in the first meeting of the second cycle was 87.50% categorized well, increased in the second cycle a second meeting with a value of 95.83% categorized very well. Activities of students at the first meeting of the first cycle was 58.33% unfavorable category, increased in the first cycle of the second meeting with a value of 70.83% categorized enough. At the first meeting of the second cycle also experienced a 83.33% peningaktan activity is categorized well, at the second meeting of the second cycle also experienced a 91.67% increase in activity with very good category. Improved learning outcomes. The average value of the student base score is 60.07, increasing to 63.45 with the thoroughness of 31.03%, the average UH First cycle completeness 63.45 with 41.38% while the average UH Cycle II 75.34 by 93.10% completeness. Key Words: STAD, Mathematics learning outcomes